Analysis of Damage to Starter Generator Set Dynamo at Jayapura Aviation Polytechnic - Wahyu Bimantara Hadi Saputra; Nurhedhi Desryanto; Yenni Arnas (JRSI (Jurnal Rekayasa Sistem dan Industri), 2026)
This study examines the reliability of backup power supply systems at Politeknik Penerbangan Jayapura, focusing on a 1,000 kVA diesel generator used to support critical loads such as server rooms, emergency lighting, and laboratory facilities. In early 2025, several failures occurred when the generator could not operate due to damage in the starter system, particularly the starter motor, leading to temporary power outages. The research aims to identify the causes of these failures, assess their impact on system reliability, and propose preventive technical measures. A field study with a descriptive comparative approach was conducted through direct observation, technical measurements (battery voltage, starting current, and engine speed), documentation, and interviews with technicians. The findings reveal that the main cause of failure is mechanical damage to the pinion gear due to excessive wear, preventing proper engagement with the flywheel. This issue is worsened by declining battery performance and insufficient preventive maintenance. As a result, the starter motor cannot generate enough torque to start the engine. The study recommends scheduled maintenance, routine inspections, and timely component replacement.